Complex properties management: Preventive and planned conservation applied to the Royal Villa and Park in Monza. Issue 2 (1st June 2018) - Moioli, Rossella; Boniotti, Cristina; Konsta, Anthoula; Pili, Alessandra
Abstract : Purpose: The paper will present the case study of preventive and planned conservation applied to the Royal Villa and Park of Monza, which is one of the pilot projects within the general framework of Monza and Brianza Cultural District. Starting from an in-depth analysis of the Royal Villa, which represents a recent conservation and valorisation intervention developed by both public and private subjects, the purpose of this paper is to define an operative model for the management of complex properties, at communicating good practices for the maintenance of the built heritage and at identifying the priorities for the interventions. Design/methodology/approach: The research project foresaw a first collection of data and information related to the previous conservation activities executed upon the case study, the design of a conservation plan in all its parts (technical handbook, conservation programme, economic budget, user handbook) through an information system dedicated to the conservation of built cultural heritage, and its fulfilment. In the meantime, a context analysis of the Royal Villa and Park of Monza was developed, with a specific attention to the diversified historical buildings located in the park. Findings: The action research carried out has been evaluated in the framework of upstream perspective theories. This enabled to highlight the importance of an integrated approach; of the need of sharing the collection of data in order to set up evidence-based policies; and of the need to enhance the skills of involved professionals and decision makers. Originality/value: A progress in protection measures, the understanding of conservation and valorisation as preventive activities, effectiveness of private business models for maintenance, dissemination of good practices, and creation of a network of local stakeholders.